Sexualized bodies of the Filipino: Pleasure and desire as everyday truth and knowledge - Contreras, Antonio P. (Animo Repository, 2014)
This paper will show that attempts to control the body in late capitalism is replete with symbolic violence, but Filipinos have not succeeded in confining the body, thereby validating Foucault's (1980) critique of the repressive hypothesis. Ordinary narratives about the body in the Philippines exist not in the context of a settled template of silenced debates and repressed desires, but in the explosion of discourse and contestations, and of an intricate articulation between popular knowledge and truth, on one hand, and the ordinary and everyday experience of pleasure and desire, on the other.